Management approach to patients with premalignant lesions of the stomach - V. V. Tsukanov; O. S. Amelchugova; A. V. Vas'yutin; N. N. Butorin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze modern aspects of management of patients with premalignant changes in the stomach.Key points. According to requirements of system OLGA or OLGIM application of modern endoscopic methods and morphological investigation is necessary for expert diagnostics of atrophy, metaplasia and dysplasia in the stomach. Detection of Helicobacter pylori infection and its eradication are important principles of management of patients with stomach premalignant lesions.Conclusion. Monitoring methods of patients with stomach mucosa dysplasia are specified. Modes of H. pylori eradication are presented.